Interface damage monitoring of assembled GFRP-UHPC composite beams using piezoelectric smart aggregate. (1st December 2022) - Qian, Hui; Zhu, Yunyun; Liang, Penghui; Zhang, Pu
Abstract: Glass fiber reinforced plastic reinforcement (GFRP) and ultra-high performance concrete (UHPC) were combined into a new composite beam, which was applied in ocean engineering to improve the durability of structures. To enhance the stiffness and durability of composite beam and lower the cost of structure, prefabricated construction technology was adopted to reserve holes for pouring UHPC. Through the quasi-static test of prefabricated GFRP-UHPC composite beams, the interface between concrete and GFRP was monitored using piezoelectric smart aggregate. The damage index was obtained in accordance with wavelet packet energy analysis theory to examine the interface damage of prefabricated composite beams. Experimental results show that active monitoring of assembled GFRP-UHPC composite beams with piezoelectric smart aggregate can effectively reflect the degree of interface peeling damage of composite beams. The monitoring results reveal that interface damage of specimens with reserved continuous holes is less than that of specimens with reserved discontinuous holes. Moreover, peeling damage will occur not only between GFRP and UHPC, but also at the interface between concrete and UHPC.